Determinants of capital structure and its optimization - Křivská, Romana; Valach, Josef, 1933-2025; Marek, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2009)
The finding of optimal debt-to-equity structure, taking into account the determinants which influence Capital Structure, is an ongoing problem in Corporate Finance. It is confirmed in theory as well as in practice in the world of Corporate Finance. There are several theoretical approaches to optimal Capital Structure, nevertheless, in practice none of these theories can be fully confirmed. The aim of the dissertation is the analysis of determinants of Capital Structure and the assessment of the application of current optimal Capital Structure theories. The significance of the individual determinants of Capital Structure is evaluated and the relationship between Leverage and certain determinants is analyzed, based on regression and correlation analysis. These tasks are based on an international point of view followed by the empirical application to mining companies in the Czech Republic and Europe. The dissertation is divided into 3 main parts which include a theoretical part, an analysis of current findings and, finally, an empirical analysis. In the theoretical part, the basic terms used in the topic of Capital Structure are defined by their different meanings in theory. These are Capital, Capital Structure and Leverage. The determinants of Capital Structure were specified with respect to the optimal Capital Structure theories, and the determination of optimal debt ratio is discussed. The analysis of current findings is focused on the empirical verification of optimal Capital Structure theories, on international examples, and on the example of the Czech Republic. Attention is dedicated to understanding the significance of determinants of Capital Structure and the determination of the relationship between Leverage and determinants of Capital Structure.
A comparison of the theoretical and empirical findings is made between a group of American and European companies, and between three groups of countries (developed countries, developing countries and transition countries, including the Czech Republic). The empirical part is dedicated to the analysis of determinants of Capital Structure of mining companies in the Czech Republic and Europe. The analyzed determinants are size, profitability, tangibility of assets, and a non-debt tax shield.
Vedoucí práce: Josef Valach
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2009
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2009
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor disert. práce]; disertace; dissertations